PENGEMBANGAN ASSESSMENT PEMBELAJARAN FISIKA BERDASARKAN KISI-KISI STANDAR KOMPETENSI LULUSAN (SKL) UJIAN NASIONAL TINGKAT SMA/MA TAHUN 2013 - Wicky Andrian (Universitas Negeri Padang, 2014)
This study originated from the fact that there are school students who did not pass the national exam . One of effort that does by the educational unit is additional subjects for the preparation of national exams. Based on this issue, study conducted with the aim of producing a Physics Assessment book based SKL of national exam level SMA/MA which a valid and practical . The type of research conducted Research and Development ( R&D ). The instrument used to collect data is: expert validation sheet, questionnaire of teacher responses and test trial. Validity test conducted by seven validators with the overall appearance suggests that the book is valid with an average value of 78,96. The test results in the practicality aspect, shows this highly practical book for teachers with an average value of 81,98. The results of a limited trial of exercises test are good. As results, it’s concluded that the Physics Assessment Book based SKL national exam level of SMA/MA is valid and practical.